Aging of recycled aggregates mortars by drying-wetting cycles. (8th November 2021) - Sainz-Aja, J.; Carrascal, I.; Polanco, J.; Cimentada, A.; Thomas, C.; Brito, J.
Highlights: The use of different types of waste from the railway superstructure can be used in the manufacture of recycled mortar. The influence of the fine aggregate of different natures on the durability of the recycled mortar has been analyzed. The durability of recycled mortars is notably less when is aged using distilled water, compared to sea water or water with sulphates. The microstructure reveals the damage caused by the crystallization of salts inside the holes or pores of the cement paste of the mortar. Abstract: Due to the large amount of CO2 emissions produced nowadays by the construction sector, the scientific community is looking for measures that will bring constructions to the be as environmental-friendly as possible. One of the most popular lines of research is the use of construction waste as recycled aggregates for the production of recycled aggregates concrete. Regarding the use of coarse recycled aggregates, there are a large number of studies that validate their use at both a mechanical and durability levels. Regarding the use of fine particles, which are inherent to the existence of coarse particles, it is necessary to increase the existing knowledge before they can be widely used. In this paper, the authors have sought to isolate the weakest part of those concrete mixes with exclusively recycled aggregate, i.e. a mortar made exclusively with fine recycled aggregates, in order to analyse the effect of drying-wetting cycles on mixes with recycled aggregates only. Specifically, three types of fine aggregates were used, one natural silica aggregate, one aggregate from crushed ballast and one from crushed sleepers. The mortars made with these aggregates were subjected to 50 durability cycles in distilled water, seawater and water with sulphates. Mechanical, visual and microstructural tests were carried out to analyse the effect of each of these environments on each of the mortars.